Development of Chemistry Lab Practical Application for Secondary Student in Virtual Reality: ChemisTry - Andi Azis, Halimah Nur; Wahid, Noorhaniza (Applied Information Technology And Computer Science, 2025)
Virtual Reality (VR) has emerged as a significant technological innovation in the age of globalization and technological advancement, offering users an immersive 3D experience within computer-generated environments. VR applications have found in various sectors, including medicine, video games, tourism, industry, and education. The existing applications for Chemistry practical labs that are available are yet to be implemented, especially in VR. Therefore, this project is proposed to develop a practical chemistry lab application to help students in secondary school practice doing their experiments. This project explores the development and significance of "ChemisTry," a VR application designed to assist secondary school students, particularly those in forms 4 and 5, in mastering their practical chemistry skills. This project uses the TRES-D methodology for its development. It covers experiment based on the syllabus from Kurikulum Standard Sekolah Menengah (KSSM). User acceptance testing for the ChemisTry application with 30 students from SMK Seri Gading, using TAM and SUS, yielded positive feedback, with 88.8% students strongly agree and agree with the statements. Overall, the application is deemed suitable for virtual Chemistry lab practicals.